The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/su12177037
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Energy Efficiency in the Food and Beverage Industry: A Human-Centered Design Approach

Abstract: Energy efficiency in companies is addressed by established tools or procedures, such as energy audits or the implementation of an energy management system in accordance with the Energy Efficiency Directive. Both options indistinctly provide sufficient information for companies to identify opportunities for improvement and savings in their energy costs. However, the influence of cultural and behavioral aspects on employees and the organizational and structural configuration of companies impacts the effectivenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…EnPIs play an important role at different levels of energy management [55]. However, there is more focus on the aggregate level, leaving out sub-systems and equipment levels in the industrial organizations [36].…”
Section: Implications Of Indicators On the Industrymentioning
confidence: 99%
“…EnPIs play an important role at different levels of energy management [55]. However, there is more focus on the aggregate level, leaving out sub-systems and equipment levels in the industrial organizations [36].…”
Section: Implications Of Indicators On the Industrymentioning
confidence: 99%
“…The E2DRIVER project is an improvement of the INDUCE program [1], which in its conclusions determined that the methodology can be a very useful tool to promote energy efficiency in a company of any industrial or service activity in Europe, due to its flexibility and adaptation to any environment. In addition, it improves the results of the actions carried out [2]. In this case, the methodology developed is implemented in SMEs in the automotive sector.…”
Section: Introductionmentioning
confidence: 99%
“…However, the main challenges facing the industry are high energy and water consumption, large waste generation as well as emissions of CO2 to the atmosphere (Scheller et al, 2008). The food and beverage industry is the biggest consumer of energy and causes 67% of the greenhouse gas emissions (Millán et al, 2020). It has been reported that, the major consumers of electricity in breweries are refrigeration (44%), packaging (20%), and compressed air (10%) (Scheller et al, 2008).…”
Section: Introductionmentioning
confidence: 99%